(untitled) (Docentes 2.0 Journal, 2021)
On the world scene, Information and Communication Technologies (ICT) are part of educational policy in countries, especially the most advanced ones. The purpose of this article was to determine the influence that educational technologies have had on the teaching processes of international finance in university students. The process carried out from a pedagogical perspective was founded from the theoretical foundations of connectivism, which explains complex learning in a rapidly evolving digital social world. The methodological structure was oriented from a qualitative documentary approach with a descriptive type. For the collection of information, a bibliographic record card was used as an instrument, were used a document review procedure. Six successful experiences related to finance and economic sciences were collected and analyzed, both in the international context and at the national level. The results obtained show that ICTs have had a significant impact, reaching exponential growth in educational contexts, since the declaration of a pandemic issued by the WHO. This situation led to the dynamics between teachers and students being mediated by technology; however, in the financial field, few successful experiences reflect the impact of technologies, a fact that shows pedagogical shortcomings in economics teachers, being essential to promote the use of ICT tools and digital resources in their pedagogical practices teaching.